Natural occurrence of fumonisins in corn puff in Argentina - Federico, Francisco Javier; Funes, Gustavo J.; Salas, Maria P.; Resnik, Silvia L. (Springer, 2019)
Maize presents a substantial contamination by fumonisins (FB) throughout the world. In particular, Argentina presents a high frequency of positive samples and levels of up to 10,000 μg/kg of total FB, depending on the harvest campaign studied. Corn puff, an extruded product of high consumption among children and adolescent populations, was analyzed with the aim of determining the presence and levels of fumonisins B1, B2 and B3. In the present study, 20 samples of different brands were collected from commercial stores. Two solvent systems, two types of agitation, and the number of extractions were tested in order to find the most suitable method to establish the level of fumonisins in corn puff. Extracts were analyzed by high performance liquid chromatography (HPLC) with fluorescence detection. A C18 column and precolumn derivatization with orthophtalaldialdehyde were utilized. The average of fumonisins found in 20 samples was 257.5 μg/kg (n = 19), 70.4 μg/kg (n  = 14) and 73.3 μg/kg (n  = 6) for FB1, FB2 and FB3, on positive samples, respectively. These are the first analyses in Argentina of this type of product, highlighting the need to continue the studies in the processing industries because, despite the extrusion process that the raw material suffers, a sample was found with a contamination of 1,649 μg/kg total fumonisins.